GLOBAL PREVALENCE OF CHRONIC GLOMERULONEPHRITIS AMONG KIDNEY DISEASES - Dildora Abdujalilovna Tojiboyeva, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Chronic glomerulonephritis (CGN) is a progressive immune-mediated inflammation of the renal glomeruli, often resulting in a gradual decline in kidney filtration function. It is classified as a type of chronic kidney disease (CKD) and represents a significant public health challenge worldwide.Recent epidemiological studies indicate that CGN-related CKD affects millions of individuals globally. In 2019, approximately 17.3 million people were estimated to live with CKD caused by CGN. Between 1990 and 2019, the incidence of CGN increased by nearly 81%, a trend associated with population growth, longer life expectancy, and aging populations. During the same period, mortality related to CGN nearly doubled, reflecting the growing burden on healthcare systems.CGN can occur at any age but is most frequently diagnosed among middle-aged and older adults. Some cases are also reported in children and adolescents. Gender differences have been observed, with higher prevalence reported in males compared to females, highlighting the importance of demographic factors in disease screening and prevention strategies.